The United States, Israel, and the Affective Lives of Moral Injury: A Genealogy of Lawfare’s Emotional Presuppositions - Loefflad, Eric (Athena – Critical Inquiries in Law, Philosophy and Globalization, 2025)
While ‘lawfare’ is subject to numerous understandings, I argue that a neglected line of inquiry surrounding lawfare is the emotional presuppositions invoked by the usage of this term. Viewing said emotions as deeply linked to the formative American and Israeli invocations of this particular word, I advance the argument that the use of the term ‘lawfare’ expresses a fear of ‘moral injury’ whereby acting contrary to stated values might impair combat efficiency. Exposing this point, I argue, demands a genealogical investigation of the varied intersections of law, war, and morality within the American and Israeli experiences preceding the articulation of ‘lawfare’ immediately after 9/11. I focus here on the interlinkage of various events, and the diverging ideologies that framed them, from experiences of Nazism to the Vietnam War to Israel’s various multi-scalar wars against both its neighbours and the Palestinians. Through exposing these histories and their affective legacies, we gain deeper insights into the long shadows of moral injury that lawfare discourse seeks to pre-empt. Such an exercise possesses great value when navigating a geopolitical future that, despite its many uncertainties, will likely include increasingly prolific invocations of ‘lawfare’ that stem from deeply rooted and historically textured emotions.